2019
DOI: 10.1038/s41467-019-11283-w
|View full text |Cite
|
Sign up to set email alerts
|

Tens of thousands additional deaths annually in cities of China between 1.5 °C and 2.0 °C warming

Abstract: The increase in surface air temperature in China has been faster than the global rate, and more high temperature spells are expected to occur in future. Here we assess the annual heat-related mortality in densely populated cities of China at 1.5 °C and 2.0 °C global warming. For this, the urban population is projected under five SSPs, and 31 GCM runs as well as temperature-mortality relation curves are applied. The annual heat-related mortality is projected to increase from 32.1 per million inhabitants annuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
94
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(96 citation statements)
references
References 53 publications
2
94
0
Order By: Relevance
“…Moreover, some of these studies were based on the older climate projection scenarios [3,20] while others have not taken into account the demographic changes in the future [23] or considered only a limited number of climate and population change scenarios [22]. Some recent studies on mortality projection due to climate change take into account the population aging, but focus on heat-related impacts ignoring the cold-related impacts [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some of these studies were based on the older climate projection scenarios [3,20] while others have not taken into account the demographic changes in the future [23] or considered only a limited number of climate and population change scenarios [22]. Some recent studies on mortality projection due to climate change take into account the population aging, but focus on heat-related impacts ignoring the cold-related impacts [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The data also projected that heat stress would become a significant health hazard in >95% of countries in the world by the end of this century [27]. Climatic modelling using data from 27 cities in China projected an increase in the annual heat-related mortality by 1.5-2-fold (48.8-67.1/million) at 1.5 • C warming of mean surface temperature, and by 1.8-2.5-fold (59.2-81.3/million) at 2 • C warming of mean surface temperature [26]. The combined heat-related mortality among the 831 million inhabitants across the 27 cities would be >28,000 annually if mean surface temperature is increased by 1.5-2 • C [26].…”
Section: Impact Of Global Warming On Human Life and Functionsmentioning
confidence: 99%
“…Climatic modelling using data from 27 cities in China projected an increase in the annual heat-related mortality by 1.5-2-fold (48.8-67.1/million) at 1.5 • C warming of mean surface temperature, and by 1.8-2.5-fold (59.2-81.3/million) at 2 • C warming of mean surface temperature [26]. The combined heat-related mortality among the 831 million inhabitants across the 27 cities would be >28,000 annually if mean surface temperature is increased by 1.5-2 • C [26]. In south Korea, heat related mortality in 2090 was projected to increase by 5.1-fold under a 3-4 • C increase in surface temperature, and by 12.9-fold if surface temperature is increased by >4 • C [29].…”
Section: Impact Of Global Warming On Human Life and Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that high temperatures can lead to fatigue, dizziness, increased breathing, and increased heart rate [3]. More serious situations can even endanger life and cause death [4]. An urban park is a main place for outdoor activities of citizens and also an important part of urban green space system, which plays an important role in mitigating the urban heat island effect and improving the outdoor thermal comfort.…”
Section: Introductionmentioning
confidence: 99%